IMPLEMENTASI PENYELENGGARAAN REKOMENDASI TEKNIS BIDANG PERTAMBANGAN MINERAL DAN BATUBARA PASCA TERBITNYA UNDANG-UNDANG NOMOR 23 TAHUN 2014 DI PROVINSI BANTEN TAHUN 2016 - Ratna Wurjandari; Leo Agustino; Suwaib Amirudin (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2019)
This study aims to explain the process of transfer of authority in mineral and coal mining from the district / city to the Banten Provincial Government. Including the constraints and implications of the transition of authority over the implementation of good governance mining practices in Banten Province after the issuance of Law Number 23 Year 2014 concerning Regional Government. This study uses descriptive qualitative methods. The results of the study indicate that the process of transferring mineral and coal authority in Banten Province still encountered several obstacles and obstacles. First, mining business licenses are not permits that are only administrative in nature but are closely related to technical and non-technical readiness in the field. Secondly, the authority to administer mining business licenses that have been delegated since the end of 2014 to the Banten Provincial Government has brought its own constraints to the Banten Provincial Office of Energy and Mineral Resources (Mining and Energy Service) as the technical service provider for technical recommendations. Third, is the delegation and submission of mining data in Kabuaten / cities throughout Banten Province. Fourth, is the overlapping financial obligations imposed on applicants for mining business licenses. The Banten Provincial Government has also not yet prepared regulations related to the issue of mineral and coal mining. This condition will have an impact on the application of good meaning practice in Banten Province, where in its implementation it must pay attention to environmental aspects, community development. Keywords: Mining, the transition of authority, good mining practice